1997
DOI: 10.1073/pnas.94.24.13005
|View full text |Cite
|
Sign up to set email alerts
|

The N terminus of the Drosophila Numb protein directs membrane association and actin-dependent asymmetric localization

Abstract: Drosophila Numb is a membrane associated protein of 557 amino acids (aa) that localizes asymmetrically into a cortical crescent in mitotic neural precursor cells and segregates into one of the daughter cells, where it is required for correct cell fate specification. We demonstrate here that asymmetric localization but not membrane localization of Numb in Drosophila embryos is inhibited by latrunculin A, an inhibitor of actin assembly. We also show that deletion of either the first 41 aa or aa 41-118 of Numb el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
78
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 36 publications
(56 reference statements)
2
78
0
Order By: Relevance
“…Thus, NIP appears both necessary and sufficient for the recruitment and retention of Numb in the plasma membrane. Interestingly, a 76-residue fragment upstream of the PTB domain was localized to the neuroblast membrane when expressed in Drosophila (34). Because this fragment does not interact with NIP in vitro, it is likely that it may interact indirectly with NIP or that other mechanisms of Numb membrane localization exist.…”
Section: Nip Is a Membrane Anchor Formentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, NIP appears both necessary and sufficient for the recruitment and retention of Numb in the plasma membrane. Interestingly, a 76-residue fragment upstream of the PTB domain was localized to the neuroblast membrane when expressed in Drosophila (34). Because this fragment does not interact with NIP in vitro, it is likely that it may interact indirectly with NIP or that other mechanisms of Numb membrane localization exist.…”
Section: Nip Is a Membrane Anchor Formentioning
confidence: 97%
“…Numb does not contain a transmembrane segment or a lipid anchor, and therefore, its recruitment to the plasma membrane may be mediated by a lipid and/or a protein component of the membrane. The N-terminal region of Numb, including the PTB domain, was shown to be necessary for the membrane recruitment and asymmetric localization of Numb (34). Although the PTB domain was originally identified as a protein module that interacts with NPXpY-containing sequences, some members of the family, such as the Shc and Dab1 PTB domains, are also capable of binding to acidic lipids (46,47) and are therefore implicated in membrane localization.…”
Section: Nip Is a Membrane Anchor Formentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, mutation of the myristoylation site of Numb also failed to affect membrane localization, although truncation of the first 40 amino acids of the N-terminus caused the protein to accumulate in the cytoplasm (Knoblich et al, 1997). It remains to be seen if Numb contains a bipartite localization motif similar to that seen in Nullo and whether the independent membrane targeting activity of myristoyl groups and basic clusters is a common occurrence in Drosophila.…”
Section: N-terminal Motifs Control the Localization Of Nullo Proteinmentioning
confidence: 98%
“…Although the majority of these genes have been characterized genetically and developmentally, only a handful have actually been shown to be myristoylated (Neel and Young, 1994;Teng et al, 1994;Rossi et al, 1999), and the in vivo role of the myristoylation site has been studied only in the neural protein Numb (Knoblich et al, 1997). Using a yeast NMT system (Duronio et al, 1990), we demonstrated that Nullo is modified by the addition of a myristoyl group, and this is prevented by the substitution of alanine for glycine in position 2.…”
Section: N-terminal Motifs Control the Localization Of Nullo Proteinmentioning
confidence: 99%